Globalising the German energy transition - Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2012)
With its twin objectives of phasing out nuclear power and decarbonising the energy supply, the German energy transition is of worldwide significance. All the more so if the challenges of climate change and sustainable energy security are taken seriously, for they can only be tackled globally. Although the international dimension of the energy transition has been largely ignored to date, internationalisation - alongside Europeanisation - represents an important aspect of climate protection and security of supply, as well as cost efficiency and competitiveness. If the energy transition succeeds, it will serve as an international model, demonstrating the objectives, options and development paths that are needed to deal with the unparalleled imponderables and growing heterogeneity of the global energy system. The allure of the German energy transition represents an important foreign policy resource, of which full use should be made. That means applying and refining a variable geometry of bi- and multilateral energy relations. If the energy transition is successful, it will raise Germany's international profile, while failure would have significant international repercussions
Keywords: 320